Comparison of computational fluid dynamics–discrete element method and discrete element method simulations for a screw conveyor. Issue 1 (12th December 2019) - Wang, Shuyan; Ji, Yu; Wang, Shuqing; Chen, Yujia; Tian, Ruichao; Ma, Yimei; Sun, Qiji
Abstract: Flow behavior of particles is simulated by means of discrete element method (DEM) in a screw conveyor. The gas flow is considered by the Euler model. The subgrid scale model turbulence model is applied to solve gas turbulence. A detailed description of the model equations applied has been presented. The comparison between computational fluid dynamics (CFD)‐DEM (i.e., considering gas flow) and DEM (i.e., not considering gas flow) simulation results is performed. Predicted mass flow rate with CFD‐DEM model is in better agreement with experiments by Roberts and Wills comparing with DEM results. The effects of incline angle and filling rate on the flow behavior of particles are predicted. The simulation results show that the gas flow has a major impact on particle flow behavior at a high rotation speed, whereas the velocity of particles increases with an increase of rotation speed. As the filling rate rises, both the translational granular temperature and the rotational granular particle temperature decline, which means that the particles fluctuation turns weak. While with an increase of incline angle, from the horizontal to vertical, the translational granular temperature is increased, but the rotational granular temperature reduces and then goes up. In brief, translational motion is a main mode of motion in a screw conveyor.